Herramientas educomunicacionales en la proyección de propuestas inclusivas - Ordoñez Icaza, Karla Xiomara (2024)
Currently, educommunicational tools have provided direct help to the educational process, due to their innovative strategies and the opportunity to create skills in students and improve the student environment. In this research, the Miraflores Educational Unit will be addressed as a case study to demonstrate the contribution of these tools with an inclusive approach. Recognize the use that teachers have had of these strategies and the results in their students. In addition, the contribution of technology in education will be seen from a professional perspective, and the importance of inclusion in society, family and, above all, in the educational process.